MAKNA UCAP – UCAP TOPENG SIDHAKARYA DALAM UPACARA PIODALAN AGUNG DI PURA DALEM AGUNG PADANGTEGAL - Wahendra, I Putu (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
One form or manifestation of the art of the saint is the Sidhakarya Mask Dance. This dance is performed in every large-scale yadnya ceremony. This dance is a representation of Brahmana Keling in the story of the Babad Dalem Waturenggong. One of the areas in Bali that performs this dance is the Padangtegal Traditional Village. In the Padangtegal Traditional Village, in every implementation of the Piodalan Agung ceremony at the Pura Dalem Agung Padangtegal, a sacred mask or Sidhakarya tapakan is danced. In its performance, the dance contains sayings or sentences in the Kawi language spoken by the dancer. The problems that can be formulated in this study are: (1) what is the meaning of the sidhakarya mask sayings?, (2) what concepts are contained in the sidhakarya mask sayings and (3) how is the existence of the sidhakarya mask sayings in terms of situation, time and environment?, In this paper, the theory of meaning is used to dissect the formulation of the problem in this study. The methods used in this study are observation, interviews and literature studies. The data was then analyzed using data reduction, data presentation and conclusion drawing methods. The results obtained from this paper are that the sayings of the Sidhakarya mask in Pura Dalem Agung Padangtegal are an introduction to the offerings of the Piodalan Agung ceremony and complement all its shortcomings. The sayings of the sidakarya also contain concepts of Hindu philosophy. The concepts contained in it are the concepts of Nirguna and Saguna Brahman, the concept of Siwa Sidhanta and the concept of Tantra, and the existence of the sayings of the sidhakarya mask is supported by the aspects of desa kala and patra as determinants of the sacred or profane of an art form.